Methane Oxidation Over Pd Supported on Ceria–Alumina Under Rich/Lean Cycling Conditions - Fouladvand, Sheedeh; Schernich, Stefan; Libuda, Jörg; Gronbeck, Henrik; Pingel, Torben; Olsson, Eva; Skoglundh, Magnus; Carlsson, Per-Anders (Topics in Catalysis, 2013)
Catalysts with highly dispersed palladium on alumina, alumina doped with 20 wt% ceria and ceria have been prepared, characterized and examined for net-lean methane oxidation. In particular, the activity and selectivity were investigated during rich/lean cycling of the feed. The ceria content is found to influence both the general and the instantaneous activity responses. The results indicate that the active phase of palladium changes between reduced and oxidised Pd during the rich/lean cycling, and that the process is influenced by the presence of ceria.